Analisis Pengaruh Kualitas Layanan terhadap Kepuasan dan Loyalitas Konsumen pada Perusahaan Ritel Alfamart - Bahjatul Mardiah; Sri Maryanti; Suharti Suharti (Valid: Jurnal Ilmiah, 2022)
The purpose of this research is to find out whether the quality of service seen from the variable tangibles, responsive, reliability, assurance and empathy simultaneously and partially have a significant effect on customer satisfaction and loyalty. This type of research includes research associative which states the relationship between two or more variables. The population in this study are customers who make purchases of goods at Alfamart Mujur. Sampling technique using purposive sampling with a sample of 150 people. The results of this study indicate that the quality of service seen from the variable tangibles, responsive, reliability, assurance and empathy simultaneously (together) have a significant effect on customer satisfaction, then the variable Responsive (X2) is a variable which has the greatest and most significant influence on the variable of customer satisfaction. Service quality as seen from tangibles variable, responsive, reliability, assurance, empathy and consumer satisfaction simultaneously (together) have a significant effect on consumer loyalty, then the variable consumer Satisfaction (X6) is a variable that has an influence the largest and most significant variable on consumer loyalty.